2016
DOI: 10.1017/s0025315416000680
|View full text |Cite
|
Sign up to set email alerts
|

Comparative morphology of the urohyal bone of fishes collected from the Persian Gulf and Oman Sea

Abstract: The urohyal is incorporated within the hyoid and branchial arches and performs a significant role in the mouth opening-closing mechanism of fishes, and is considered a synapomorphy of teleostean fishes. Morphological variation of the urohyal, in terms of size and shape parameters, can allow species identification. Morphology of the urohyal in 49 species belonging to 43 genera and 29 families from the Persian Gulf and from the Oman Sea were compared using size and shape measurements. The results examine the sui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
7

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 30 publications
0
8
0
7
Order By: Relevance
“…Reproductive isolation between G. cinereus and G. simillimus has resulted in morphological variation that can be quantified by analysing the shape of the bodies, urohyal bones or sagittae otoliths, which are important for taxonomic purposes (Arratia & Schultze, ; Baremore & Bethea, ; Chollet‐Villalpando et al, ; De La Cruz‐Agüero et al, ; Jawad, Khahe‐Jahromi, Teimori, Mehraban, & Esmaeili, ; Nolf, ; Reichenbacher, Sienknecht, Kuchenhoff, & Fenske, ). The discriminant power of body shape was higher than otolith and urohyal shape.…”
Section: Discussionmentioning
confidence: 99%
“…Reproductive isolation between G. cinereus and G. simillimus has resulted in morphological variation that can be quantified by analysing the shape of the bodies, urohyal bones or sagittae otoliths, which are important for taxonomic purposes (Arratia & Schultze, ; Baremore & Bethea, ; Chollet‐Villalpando et al, ; De La Cruz‐Agüero et al, ; Jawad, Khahe‐Jahromi, Teimori, Mehraban, & Esmaeili, ; Nolf, ; Reichenbacher, Sienknecht, Kuchenhoff, & Fenske, ). The discriminant power of body shape was higher than otolith and urohyal shape.…”
Section: Discussionmentioning
confidence: 99%
“…Afterward, the urohyal bones were stored in small tubes, cataloged and deposited in the Zoological Museum of Shahid Bahonar University of Kerman (ZM-SBUK). The lateral view of the urohyal bones was photographed from the left side by using a Dino-Lite Camera mounted on a stereomicroscope because the lateral view of urohyal bone is an important character for species differentiation (Jawad et al, 2017). The terminology introduced in Chollet-Villalpando et al (2014) was used to describe the urohyal bone morphology (Fig.…”
Section: Preparation Of Urohyal Bone Morphological Description and Mmentioning
confidence: 99%
“…1). Urohyal maximum length (anterior to posterior distance, UL) and urohyal maximum depth (dorsal to ventral distance, UD) of the urohyal bones were measured following Jawad et al (2017). Accordingly, the E index (E = UD/UL %) was calculated to determine the relationship between the shape of the urohyal bone among the seven gobies species (Jaramillo et al, 2014).…”
Section: Preparation Of Urohyal Bone Morphological Description and Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Sci., 19/2, 2018, 356-365 357 The urohyal bone is considered as synapomorphy for the members of teleost fishes (De Pinna, 1996). Further studies indicated that morphological features of the urohyal bone can be used to discriminate fish families, genera and even species (Arratia & Schultze, 1990;Jawad et al, 2016), and that urohyal bone has taxonomic significance (Kusaka, 1974;Esmaeili & Teimori, 2006). Therefore, it can be hypothesized that urohyal bone contains sufficient data to disclose taxonomic and even phylogenetic relationships among the fishes.…”
Section: Introductionmentioning
confidence: 99%